The diagnosis and management of endometriosis with food : a journey : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts (by thesis) in Psychology at Massey University, Albany, New Zealand - Templeton, Kimberley (Massey University, 2020)
Endometriosis is a debilitating and all-consuming disease which effects females of reproductive age. Symptoms can include chronic pain, nausea, headaches, body aches, and digestive and urinary issues. Endometriosis is unpredictable, as while there are four stages of the disease these stages often do not reflect the symptoms the women experience. Endometriosis is difficult to manage due to the unique symptom presentations and where the medical professionals’ focus is primarily on pain management with medication. Women often resort to trialling other strategies to try to mitigate the impact this disease has on all areas of their life including social life, work and education, relationships and hopes for the future. The use of diets and food is one strategy that has helped some women to manage their symptoms, but these food restrictions also make life more difficult in terms of maintaining relationships. The aim of this study was to explore women’s experiences of living with endometriosis with a focus on how women used food and diet. The feminist approach of this study privileged the women’s voices as experts in endometriosis. This research utilised two semi-structured interviews and food diaries to explore how eight New Zealand women live with endometriosis. Thematic analysis revealed six themes; impact on life, lack of education, mental and emotional impact, judgement/perceptions, community, and learning moments. All the women had trialled diets in an effort to take back control, resist the medical dominance in treatment plans and feel healthier. The women talked of the sacrifices they had made by being on diets such as not attending social events as there would be no food to eat, but where they also discussed sacrificing their health and at times causing flare-ups by abandoning their diets so they could socialise. While the women critiqued medical professionals for their lack of knowledge and education, they also viewed themselves as lucky and discussed positive experiences of living with endometriosis.
Keywords: 520304 Health psychology